THE INFLUENCE OF BRAND AWARENESS, CUSTOMER VALUE AND TRUST TOWARD LOYALTY CUSTOMERS WITH SATISFACTION AS INTERVENING - Ayuningrum, Tyas; Mochlasin, Mochlasin (Journal of Islamic enterpreneurship and Management, 2021)
This study aims to influence Brand Awareness, Customer Value and Trust on Customer Loyalty in Bank Jateng KCPS Salatiga with Satisfaction as an Intervening Variable. This study uses quantitative methods by processing primary data through a questionnaire given to 100 respondents to the customers of Bank Jateng KCPS Salatiga. purposive sampling technique in sampling. choose the target sample or target sabmple subjectively. The data obtained were processed with SPSS Version 23. The analytical tools used include multiple linear analysis and path analysis. The results of the research test show that brand awareness has no positive and significant effect on satisfaction while customer value and trust have a positive and significant effect on satisfaction. Next is brand awareness, Trust, and satisfaction have a positive and significant effect on loyalty, while customer value has a negative and significant effect on loyalty. Brand awareness has no positive and significant effect on customer loyalty through satisfaction as an intervening variable, while customer value and trust have a positive and significant effect on customer loyalty through satisfaction as an intervening variable.